“To Own or Not to Own”. Post-socialist Housing Policy, Privatism and Regimes of Vulnerability in Prague, Czech Republic - Michal Lehečka (Archivio Antropologico Mediterraneo)
In the course of 2016, housing prices in Prague started to grow rapidly, as a result of long-term pressure generated by stagnation of construction industry, a constant influx of newcomers, speculations, shared economy platforms, etc. These globally embedded processes brought to light almost forgotten urban vulnerables: the non-owners. Prague’s current housing situation emerged from the post-socialist way of ownership liberalization and deregulation, often labelled as a regime of privatism (Hirt 2012). After the 40-year period of state-driven socialist ownership, 1990’s and 2000’s privatization transformed approx. 90% of housing stock into private property. Private ownership was thus rediscovered as a component of social status while simultaneously both city and the state abandoned any pro-active housing policy. Based on fieldwork conducted on peripheries of Prague, my paper focuses on various forms of housing vulnerability in Prague. A situation of non-owners, who have to cope with danger of displacement, will be confronted with the strategies and practices of the “newcomers” – post-Soviet region immigrants who are moving in and buying apartments in similar suburban housing estates. Examined through individual spatialities, temporalities, and hybrid regimes of in/out and local/global the paper will discuss the post-socialist housing market.